2014
DOI: 10.7567/apex.7.082301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of film formation on light-trapping properties of randomly textured silicon thin-film solar cells

Abstract: The influence of film formation on light-trapping properties of silicon thin-film solar cells prepared on randomly textured substrates was studied. Realistic interface morphologies were calculated with a three-dimensional (3D) surface coverage algorithm using the measured substrate morphology and nominal film thicknesses of the individual layers as input parameters. Calculated interface morphologies were used in finite-difference time-domain simulations to determine the quantum efficiency and absorption in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In general, it can be concluded that the optimal period increases with increasing thickness of the silicon thin film solar cell27. In order to provide a more detailed simulation of the light trapping 2D scans of the substrates and the interfaces of the solar cell have to be measured by AFM or calculated by tools modeling the film growth28293031. However, such calculations are computationally intensive.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it can be concluded that the optimal period increases with increasing thickness of the silicon thin film solar cell27. In order to provide a more detailed simulation of the light trapping 2D scans of the substrates and the interfaces of the solar cell have to be measured by AFM or calculated by tools modeling the film growth28293031. However, such calculations are computationally intensive.…”
Section: Discussionmentioning
confidence: 99%
“…A physically more precise description of the optics in randomly textured thin film solar cells can only be achieved by using rigorous simulation of the optical wave propagation [19][20][21][22]. Surface scans of the randomly textured solar cells have been used as input data in modeling such as large and randomly textured nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…We include realistic properties (complex refractive indexes) of all layers and thin sublayers, we consider realistic morphologies of not only the initial texture introduced by the substrate surface but of the internal interfaces, employing a model of non-conformal layer growth [27] in our analysis. The importance of including non-conformal layer growth in optical simulations has also been indicated by other groups [28][29][30]. In this paper, we have combined two different modelling approaches: rigorous modelling based on the finite element method (FEM) and a geometrical optics approach.…”
Section: Introductionmentioning
confidence: 99%